Culture as a dimension of country brand: the highs and lows of Brazil’s brand image - Fabiana Gondim Mariutti; Mirna de Lima Medeiros (Tourism & Management Studies)
Culturally, a country is recognized internationally as representing a significant aspect of country branding and destination branding. Therefore, the aim of this paper is to explore ‘culture’ and its associations for Brazil as a country brand dimension, which is the unit of analysis for this interpretive study in England. Thus, after focus group and thematic analyses exploring and interpreting the findings, Brazil was perceived as having a ‘diverse and positive culture’. The most surprising finding concerns the participants’ awareness of the diversity of associations with Brazil’s brand image. Initially, ‘football’, ‘Carnival’ and ‘Rio’ were the prevalent themes of the discussion, followed by ‘music’. Brazil’s next most recognized unique cultural aspects were ‘flipflops’, the ‘Amazon’, ‘carnival parades’, ‘Brazil nuts’ and the ‘Brazilian native indigenous people’. Nevertheless, Brazil’s brand image is, to some extent, more favourable than unfavourable. Thus, this study can orientate strategies for branding campaigns while fomenting business and tourism for a reputable, sustainable and successful country brand.